Peningkatan Pemasaran UMKM melalui Pemanfaatan Digital Marketing di Dusun Barong Kulon, Desa Candi, Kecamatan Pringkuku - Sarwono, Sarwono; Wahyono, Catur (ARZUSIN, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting local economic growth, including in rural areas such as Barong Kulon Hamlet, Candi Village, Pringkuku District. However, limited market access and lack of information technology utilization remain major obstacles to MSME development. This study aims to describe the current marketing conditions of MSMEs, identify the challenges they face in adopting digital marketing, and formulate appropriate strategies to enhance marketing effectiveness through digital media. This research employs a descriptive qualitative approach, using data collection techniques such as observation, in-depth interviews, and documentation involving MSME actors in the area. The findings indicate that most MSME actors still rely on conventional marketing methods, have limited understanding of digital platforms, and face infrastructure and digital literacy constraints. The proposed improvement strategies include intensive training on the use of social media and online marketplaces, regular technical assistance, and collaboration with the village government and digital communities. The study concludes that digital marketing holds significant potential for expanding MSME market reach, but requires continuous interventions to build the overall capacity of business actors. The implications of this research emphasize the importance of synergy among various stakeholders in creating an inclusive digital ecosystem for rural MSMEs.